De Novo Sequencing of a Bacterium Capable of inhibiting the growth of Ganoderma Boninense - Chin, Clament Fui Seung (Universiti Malaysia Sabah, 2014)
Eleven rhizobacteria and fifteen root endophytic bacteria were isolated from oil palm plantation site located at the school of sustainable agriculture, UMS Sandakan Campus, Sabah. Dual culture test was carried out on PDA media to select bacteria isolate with antagonistic character against Ganoderma sp. BRIUMSa. The bacteria isolates were characterized based on morphological features and identified through 16s rRNA gene sequencing and Gen-III Biolog MicroStation™ automated identification system. Results revealed degrees of inhibition toward mycelial growth of Ganoderma sp. BRIUMSa vary accordingly to the bacterial isolates. Amongst the eleven rhizospheric bacterial isolates, only seven bacterial isolates have showed positive inhibitory effect against Ganoderma sp. BRIUMSa in vitro. However, only three bacterial isolates from the genera Pseudomonas and Bacillus have showed percentage inhibitions of radial growth (PIRG) ranging from 30% to nearly 60% in the dual culture test. They were Pseudomonas aeruginosa (Pseudomonas sp. SPLUMS-1) (PIRG=59.00/0), Pseudomonas tolaasii (PIRG=48.7%) and Bacillus subtilis (PIRG=33.4%). Nevertheless, isolate B. subtilis which initially shownto inhibit mycelial growth of Ganoderma sp. BRIUMSa was eventually overlay by the fungus after 10 days of post inoculation suggesting the inhibitory effect of Bacillus sp. is only temporally. On the other hand, only one rootendophytic bacterial isolate Burkholderia cepacia (Burkholderia sp. SPLUMS-2) has showed potential inhibitory effect against Ganoderma sp. BRIUMSa with its PIRG recorded was close to 50% (48.1%). Bacterial isolates Pseudomonas sp. SPLUMS-1, Burkholderia sp. SPLUMS-2 and Pseudomonas tolaasii were further evaluated using agar amendment test and culture filtrate test. These were done by aseptically incorporating overnight bacterial culture or sterilefiltered culture filtrate into the PDA media. The percentage of inhibition (PI) value of Pseudomonas sp. SPLUMS-1 against Ganoderma sp. BRIUMSa was nearly 100% for both tests. Meanwhile, there was significant different (P<0.05) of PI value between agar amendment (20.14%) and culture filtrate (89.0%) tests for Burkholderia sp. SPLUMS-2; and 95.6% and 52.30/0, respectively for P. tolaasii. Disease severity index for seedlings pre-treatment with P. aeruginosa, B. cepacia and P. tolaasii were 150/0, 20% and 250/0 respectively, while seedlings post-treatment with the same bacteria were 200/0, 25% and 250/0, respectively in comparison to Ganoderma sp. inoculated seedlings (50%).